2016
DOI: 10.1155/2016/6234043
|View full text |Cite
|
Sign up to set email alerts
|

Bach1 Induces Endothelial Cell Apoptosis and Cell‐Cycle Arrest through ROS Generation

Abstract: The transcription factor BTB and CNC homology 1 (Bach1) regulates genes involved in the oxidative stress response and cell-cycle progression. We have recently shown that Bach1 impairs cell proliferation and promotes apoptosis in cultured endothelial cells (ECs), but the underlying mechanisms are largely uncharacterized. Here we demonstrate that Bach1 upregulation impaired the blood flow recovery from hindlimb ischemia and this effect was accompanied both by increases in reactive oxygen species (ROS) and cleave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…p53 is also a redox-regulating transcription factor via regulation of ROS production and the expression of various antioxidant enzymes (36). Increased ROS is believed to be able to activate the mitochondrial apoptotic pathway, resulting in cell death (37)(38)(39). In the present study, we found that PTE increased ROS generation both in vivo and in vitro through a p53-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…p53 is also a redox-regulating transcription factor via regulation of ROS production and the expression of various antioxidant enzymes (36). Increased ROS is believed to be able to activate the mitochondrial apoptotic pathway, resulting in cell death (37)(38)(39). In the present study, we found that PTE increased ROS generation both in vivo and in vitro through a p53-dependent manner.…”
Section: Discussionsupporting
confidence: 58%
“…We have shown that Bach1 binds to TCF4, reduces the interaction of β -catenin with TCF4, and disrupts Wnt/ β -catenin signaling by recruiting histone deacetylase 1 to the promoter of TCF4-targeted genes [14]. Our results also indicate that Bach1 reduces the proliferation, migration, and tube formation activity of human endothelial cells (ECs), induces endothelial cell apoptosis and cell-cycle arrest, and suppresses angiogenesis in mice with surgically induced hind-limb ischemia (HLI) [14, 15]. These observations suggest Bach1 as a major regulator of endothelial function and ischemia-induced angiogenesis.…”
Section: Introductionmentioning
confidence: 83%
“…Thus, Bach1 likely inhibits angiogenesis by regulating a variety of factors, including VEGF, IL-8, and HO-1. In addition, the results from our recent investigation suggest that higher levels (≈100-fold increase in mRNA expression) of Bach1 enhanced ROS production and induced apoptosis in ischemic mouse hindlimbs [15]. However, we found that a slight (≈2-fold) increase in Bach1b mRNA expression did not induce the apoptosis (data not shown) in zebrafish in the present study, which suggests that the effect of Bach1b overexpression on the developmental angiogenesis in zebrafish cannot be explained by apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that ROS, is a strong activator of AMPK, and has an important role in apoptosis [27,28,29], thus, we wondered whether ROS production is related to EPS1-1-induced AMPK activation. To evaluate the effect of EPS1-1 on ROS activity, we examined the ROS level in CT26 cells by DCF-DA staining.…”
Section: Effect Of Ros On Eps1-1-induced Ampk Activationmentioning
confidence: 99%